ANALISIS PENGENALAN MATERI DAN PENGAJARAN IPS DI SEKOLAH DASAR - Ayu Dewi Lestari K; I Nyoman Sudirman; Ni Kadek Duwi Apriliani; Ni Putu Ayu Putri Wahyuni; Ema Jois Kore (STKIP Subang, 2026)
Social Studies (IPS) is a crucial subject in elementary education, as it plays a vital role in shaping students' knowledge, attitudes, and social skills. Through Social Studies instruction, students gain insight into social, cultural, and economic environments, as well as various events occurring in their daily lives. This article aims to analyze the introduction of subject matter and the teaching of Social Studies in elementary schools. A literature review method was employed, involving the analysis of various relevant scholarly sources. The findings indicate that the introduction of Social Studies content must be tailored to students' developmental characteristics and supported by active, creative, innovative, and contextual teaching methods. Such an approach ensures optimal achievement of learning objectives while enhancing students' understanding, participation, and critical thinking skills regarding life in society.